Protection of Customary Rights of Indigenous Communities in The Midst of National Development - Efendi Gunawan Sidiki (Journal of Adat Recht, 2026)
The customary rights of indigenous peoples are constitutional rights guaranteed by Article 18B paragraph (2) and Article 28I paragraph (3) of the 1945 Constitution of the Republic of Indonesia. However, in practice, the recognition and protection of these rights often clash with the national development agenda that is oriented towards the massive exploitation of natural resources. This article aims to examine in depth the forms of legal protection for the customary rights of indigenous peoples and to identify various challenges arising from the expansion of national strategic projects, mining, and large-scale plantations. This research uses a normative juridical method with a legislative approach, a conceptual approach, and a case approach, which are analyzed qualitatively through a literature study of laws and regulations, court decisions, and contemporary agrarian law literature. The results of the study indicate that although the normative framework for the recognition of indigenous peoples has undergone significant development, particularly through Its implementation in the field still faces structural obstacles in the form of weak inter-institutional coordination, minimal definitive determination of customary territories, and the dominance of investment interests in spatial planning policies. This article recommends strengthening the customary territory database, harmonizing sectoral regulations, and implementing the principle of free, prior, and informed consent as an absolute prerequisite for any development activity impacting customary lands. These steps are expected to create a more proportional balance between the agenda of accelerating national development and the sustainable fulfillment of the constitutional rights of indigenous communities.